Media Language Games for Junior High Indonesian Language Learning - M Agus; Siti Suwadah Rimang (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this research was to characterise the impact of using language game media to teach Indonesian, hoping to improve the language skills of eighth-grade students in Jeneponto Regency. Different treatments were administered to each group of students in this quantitative research, which followed an experimental research design. The control group received no special treatment and simply traditional approaches, whereas the experimental group was given media language games. Finding differences in learning achievement between students taught using media language games and students not taught using language games (conventional method) is a key goal of this study, which aims to inform best practices for teaching Indonesian to eighth-grade students in Jeneponto Regency. As a result, media-based language games are a powerful tool for teaching and learning Indonesian.